Evaluation of pain in patients undergoing fixed dental appliance (Journal of Pharmaceutical Negative Results, 2022)
Introduction: Pain is experienced by patients during various fixed orthodontic procedures such as placement of separators, insertion of arch wire and its activations, orthopedic appliances such as headgear, and debonding of the appliance. This study was formulated with the background that the level of pain sensation differs between conventional metal and ceramic brackets, arch wire being the same pain is an important aspect of oral health-related quality of life (OHRQOL). Understanding how patients' pain experiences during their treatment affect their quality of life (QOL) is important and the absence of pain/discomfort is important for achieving a high QOL. Aim and Objective: The objective of this study was to assess the relationship between pain and OHRQOL among patients wearing fixed orthodontic appliances and to evaluate whether patient motivation and counseling had an effect on the pain and discomfort. Materials and methods: The data collection was done , the obtained data were tabulated and entered in the MS excel sheet. Data collection were imported to SPSS, variable definition process was done using tables and graphical illustration.